First comparison of quantitative estimates of termite biomass and abundance reveals strong intercontinental differences - Dahlsjö, CAL; Parr, C; Malhi, Y; Rahman, H; Meir, P; Jones, DT; Eggleton, P (Cambridge University Press, 2014)
Termite species and functional groups differ among regions globally (the functional-diversity anomaly). Here we investigate whether similar differences in biomass and abundance of termites occur among continents. Biomass and abundance data were collected with standardized sampling in Cameroon, Malaysia and Peru. Data from Peru were original to this study, while data from Cameroon and Malaysia were compiled from other sources. Species density data were sampled using a standardized belt transect (100 × 2 m) while the biomass and abundance measurements were sampled using a standardized protocol based on 2 × 2-m quadrats. Biomass and abundance data confirmed patterns found for species density and thus the existence of the functional diversity anomaly: highest estimates for biomass and abundance were found in Cameroon (14.5 ± 7.90 g m−2 and 1234 ± 437 ind m−2) followed by Malaysia (0.719 ± 0.193 g m−2 and 327 ± 72 ind m−2) and then Peru (0.345 ± 0.103 g m−2 and 130 ± 39 ind m−2). The biomass and abundance for each functional group were significantly different across sites for most termite functional groups. Biogeographical distribution of lineages was the primary cause for the functional diversity anomaly with true soil-feeding termites dominating in Cameroon and the absence of fungus-growing termites from Peru. These findings are important as the biomass and abundance of functional groups may be linked to ecosystem processes. Although this study allowed for comparisons between data from different regions further comparable data are needed to enhance the understanding of the role of termites in ecosystem processes on a global scale.